Balancing Properties of the Booster Transformer with the Longitudinal-Transverse Regulation - Zaitsev D.; Golub I.; Tirsu M.; Caloshin D. (Problems of the Regional Energetics, 2023)
The current development of the power industry involves various kinds of FACTS, being element of the Smart Grid and controlled by power electronics used for increasing the flexibility of electrical networks. Thus, the development and research of such devices are relevant. The study object is a controller belonging to the "Sen" family of transformers, which provides regulation of voltage and power flows in networks. The aim of the work is to study the balancing properties of booster transformer, which has an extended range and higher control accuracy in various modes. The goal was achieved during research carried out on the basis of structural simulation models. The most significant result was statement that the device under study has a pronounced per-phase balancing effect, which is preserved in various modes, including reverse ones. The main result can be consider that the proposed device, in comparison with the currently existing transformers of the "Sen" family, due to the extended range and accuracy of voltage regulation, allows using it when working, both for symmetrical and asymmetric loads. It is shown that the proposed technical solution provides ample opportunities for longitudinal-transverse phase-by-phase voltage regulation. Moreover, the deviations of parameters characterizing the quality of electricity, such as modules and voltage angles, do not go beyond the limits regulated by the requirements of the standard. The results obtained allowed us to conclude that this device can be used to solve the problem of coordinating the operation of two asymmetric systems in different operating modes.